2019
DOI: 10.1002/sctm.18-0183
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stromal Cell Treatment in Patients with Osteoarthritis Results in Overall Improvement in Pain and Symptoms and Reduces Synovial Inflammation

Abstract: Patients with late‐stage Kellgren‐Lawrence knee osteoarthritis received a single intra‐articular injection of 1, 10, or 50 million bone marrow mesenchymal stromal cells (BM‐MSCs) in a phase I/IIa trial to assess safety and efficacy using a broad toolset of analytical methods. Besides safety, outcomes included patient‐reported outcome measures (PROMs): Knee Injury and Osteoarthritis Outcome Score (KOOS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC); contrast‐enhanced magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 50 publications
4
177
1
8
Order By: Relevance
“…NF-kB represents a family of inducible dimeric transcription factors that stimulates osteoarthritis and it is a pivotal factor that induces suppression of the chondrogenic potential of human osteoarthritic synovial MSCs (52). Chahal et al (75) demonstrated a reduced level of monocytes/macrophages proinflammatory IL-12 cytokine in synovial fluid levels and likely improved clinical efficacy in patient-reported outcomes after 3 months of high doses of MSCs injection in the knee (75).…”
Section: Macrophages and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…NF-kB represents a family of inducible dimeric transcription factors that stimulates osteoarthritis and it is a pivotal factor that induces suppression of the chondrogenic potential of human osteoarthritic synovial MSCs (52). Chahal et al (75) demonstrated a reduced level of monocytes/macrophages proinflammatory IL-12 cytokine in synovial fluid levels and likely improved clinical efficacy in patient-reported outcomes after 3 months of high doses of MSCs injection in the knee (75).…”
Section: Macrophages and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Early clinical data shows improvements in cartilage volume and quality [2][3][4][5][6][7] and secretion of immunomodulatory factors. Our pioneering Canadian trial (NCT02351011, clinicaltrials.gov) using autologous bone-marrow-derived MSCs showed significant improvement in symptoms and quality of life relative to baseline in osteoarthritic patients; for the first time, we showed clinically that MSCs reduced synovial joint levels of pro-inflammatory macrophages, a potent inflammatory mediator, suggestive of a possible mechanism of action [8]. Macrophages are the most prevalent immune cell in OA joints [9], are elevated in OA compared to healthy joints [10], and contribute to synovial inflammation and fibrosis, characteristic of OA.…”
Section: Introductionmentioning
confidence: 87%
“…Early clinical data shows improvements in cartilage volume and quality [1][2][3][4][5][6] and secretion of immunomodulatory factors. Our pioneering Canadian trial (NCT02351011, clinicaltrials.gov) using autologous bone-marrow-derived MSCs showed significant improvement in symptoms and quality of life relative to baseline in osteoarthritic patients; for the first time, we showed clinically that MSCs reduced synovial joint levels of pro-inflammatory macrophages, a potent inflammatory mediator, suggestive of a possible mechanism of action [7]. Macrophages are the most prevalent immune cell in OA joints [8], are elevated in OA compared to healthy joints [9], and contribute to synovial inflammation and fibrosis, characteristic of OA.…”
Section: Introductionmentioning
confidence: 87%
“…After labeling, cells underwent sequential PBS washing before and after dissociation. All cells (Fe-MSCs and unlabeled MSCs) were stained with the lipophilic fluorescent dye DiR (also called DiIC18 (7), full chemical name:…”
Section: Cell Labeling and Injectionmentioning
confidence: 99%